Revamping archival education training in Africa: insights from the Digital Records Curation Study School held in Gaborone, Botswana, 5–9 August 2019. Issue 1 (1st December 2022) - Erima, Juliet A.; Mosweu, Tshepho L.
Abstract : The importance of and need for digital curation has increased significantly in recent years owing to the myriad of risks facing digital assets. These risks include problems of hardware and software obsolescence, media fragility, rapid technological developments and the frequent absence of sufficient metadata. Additionally, digital records face risks of improper handling, corruption and alteration, unauthorized access and accidental erasure. These issues necessitate continuous discussions amongst information professionals, including records managers and archivists, on how best they can be circumvented in the face of changing technologies. Hence, digital curation has gained world-wide acceptance and recognition today as a sound strategy for ensuring the continued accessibility of digital assets. This article discusses the International Council on Archives (ICA) Programme Commission (PCOM) initiative which focuses on capacity building for records and archives management in the African region. In particular, the paper discusses the 2019 Digital Records Curation Programme (DRCP) Study School held in Gaborone, Botswana, which brought together archival educators from various countries across the African continent. The study school provided a forum for the trainers and participants to share knowledge and shape the digital curation agenda for the future, including roll-out of a newly developed digital records curation curriculum for international adoption. This paper recommends the adoption of the DRCP by archival educators in African Universities. It is also recommended that the ICA make provision for continuous professional development training for the trained archival educators.